Analyses of Economy and Creative Economic Potentials in Bogor Regency - Ariani, Nani; Sugianto, Sugianto; TW, Nunuk (Budapest International Research and Critics University, 2021)
Located between the feet of the Mount Gede and the Mount Salak, Bogor Regency is a region blessed with abundant natural potentials which can be turned into tourism objects to attract both local and overseas tourists. Such advantages cannot be found in many regions. Therefore, it is necessary for local governments to recognize and to map any benefits that the region has and to identify any sector which should receive immediate attention so that they can be the driving locomotive the development of the region. The purpose of this study is to analyze the economy, economic structure, the leading sector, creative economic potential, and strategies for developing the creative economy of Bogor regency. In terms of method, this research used secondary data with analysis of economic growth, economic structure and sectoral contribution to GRDP, LQ analysis, and Shift Share analysis. To recognize potentials of creative economy and development strategy in the future, SWOT analysis with a seven-dimensional creative economy approach was applied. The research found that the growth of Bogor Regency is the highest compared to other cities/regencies in West Java... Based on the LQ analysis, there are four business fields which have been the leading sector, or the base sector with an LQ value > 1. Shift Share (SS) analysis of Bogor Regency towards West Java province over the 2015-2019 period found that the value, the overall growth of Bogor Regency is relatively higher than that of the West Java Province. Positive Differential Shift (DS) value indicates fairly high comparative advantage. The Proportional Shift (PS) value also shows proportional composition of industrial sectors growing faster than the province of West Java. Based on the seven dimensions of the creative economy used in this research, through a SWOT analysis, it needs to be developed as a whole. Of the seven dimensions, there are two dimensions that are of priority and concern. The first is the issue of human resource development and the second is the issue of financing or capital.